PENGARUH KEPEMILIKAN MANAJERIAL, RETURN ON ASSETS DAN KEBIJAKAN LIABILITAS TERHADAP INCOME SMOOTHING PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES TAHUN 2018 -2023 - Rahayu, Sri; Talidah, Saffanah (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This research aims to determine the influence of Managerial Ownership, Return on Assets andLiability Policy on Income Smoothing in Food and Beverages Sub-Sector Companies Listed on theIndonesia Stock Exchange 2018-2023 partially and simultaneously. This type of research isquantitative research. The data source used is secondary data where sampling is determined bypurposive sampling. The number of samples in this study was 10 from the population of 66 Foodand Beverages Sub-Sector Companies. The data analysis method used is multiple linear regressionanalysis with the prerequisite of classical assumption testing and continued with hypothesistesting, namely the t test to determine the effect partially and the F test to determine itsimultaneously, with a significance level of 5%. The results of this research show that partiallyManagerial Ownership has a significant effect on Income Smoothing with results of 3.787 >2.00324 sig 0.000 < 0.05, Return on Assets (ROA) has a significant effect on Income Smoothingwith results of 6.124 > 2.00324 sig 0.000 < 0 .05 and Liability Policy has a significant effect onIncome Smoothing with the result 3.779 > 2.00324 sig 0.000 < 0.05. Simultaneously ManagerialOwnership, Return on Assets and Liability Policy influence Income Smoothing with results of18.596 > 2.769 sig 0.000 < 0.05. The Adjusted R Square value in this study was 47.2%, while theremaining 52.8% was influenced by other variables.